CHARACTERISTICS AND KINEMATICS OF RAM FROZEN-THAWED SPERM MOVEMENT WITH DIFFERENT LECITHIN TYPES - Damanik, Asman Ramadhan; Karja, Ni Wayan Kurniani; Setiadi , Mohamad Agus; Kaiin, Ekayanti Mulyawati (BRIN - Badan Riset dan Inovasi Nasional, 2025)
This study evaluated the effectiveness of animal, plant, and synthetic lecithin-based extenders in preserving local Indonesian ram semen during cryopreservation. Post-thaw sperm quality was assessed using Computer-Assisted Sperm Analysis (CASA), focusing on motility, viability, membrane integrity, and kinematics. Data were analyzed using ANOVA and Duncan’s Multiple Range Test (DMRT) at a 95% significance level. Results showed that sperm motility, viability, and membrane integrity were significantly higher (P<0.05) in the animal lecithin-based extender (53.66±1.33%, 66.45±2.50%, and 67.68±2.33%, respectively) compared to plant (51.84±0.48%, 62.98±1.94%, and 64.27±1.51%) and synthetic (50.14±0.22%, 60.72±0.81%, 62.44±1.37%) extenders. While kinematic parameters were not significantly different among groups, synthetic lecithin showed slightly higher values in velocity-related measures, whereas animal lecithin resulted in the most consistent improvement in overall sperm quality. All lecithin-based extenders met the Indonesian National Standard (SNI) for semen quality, and sperm kinematics remained within optimal fertilization values after cryopreservation.